Calculation of Temperature Fields and Stresses in Pipe-Lines - R. I. Esman (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A mathematical model and a numerical solution of the problem pertaining to non-stationary temperature fields and profile temperature stresses in multi-layer heat pipelines of various application purposes are given and obtained in the paper.The developed mathematical model is applied for calculation of temperature fields and stresses in heat pipelines with the purpose of an efficient usage of heat-transfer agent power po-tential.